Removal of ciprofloxacin by anaerobic membrane bioreactor (AnMBR) and post-treatment of AnMBR effluent - Mai, Do Thi (2018)
The presence of antibiotics has been commonly reported in the aquatic environment worldwide, and may have a substantial impact on ecosystems and human health. Of all the antibiotics present in the environment, ciprofloxacin (CIP) has sometimes been reported at extremely high concentration, in the range of mg/L. CIP is also one of the antibiotics that poses a high ecological risk, and genotoxicity and the transfer of resistance between different bacterial species were induced at concentrations as low as a few µg/L. Wastewater treatment plants (WWTP) are an important process to prevent the release of antibiotics into the environment, and of all the treatment processes available, the anaerobic membrane bioreactor (AnMBR) has considerable potential for treating wastewater, and can prevent the loss of biomass inhibited by antibiotics. However, there is a lack of data available in the literature on how effective AnMBRs are in removing antibiotics, as well as the effect antibiotics have on anaerobic digesters in general, and on the AnMBR specifically. Hence, the overall aim of this work was to explore the effect of CIP on the operation of an anaerobic batch reactor and AnMBR, and then investigate the mechanisms of CIP removal and the post-treatment of AnMBR effluent by adsorption, with the main aim of removing soluble microbial products (SMPs) and CIP. The results showed that CIP significantly inhibited the anaerobic digestion of organic matter and methanogenic activities, and volatile fatty acids (VFAs) accumulated at 0.5–50 mg/L of CIP, with the higher CIP concentration causing the strongest effect, while at 0.05 mg/L no statistical effect was observed. Furthermore, ≥ 0.5 mg/L of CIP increased low molecular weight soluble microbial products and various aromatic compounds, with p-cresol and nitrogen-containing compounds (N-compounds) dominating. Syntrophobacter and Methanothrix associated with acetogenesis and acetoclastic methanogenesis, respectively, were underrepresented in the CIP-exposed communities. However, when fed continuously to an AnMBR, no effect on performance was observed with the long-term (41 days) addition of CIP at concentrations of 0.5 ± 0.1 mg/L, and during the transition state (11 days) at concentration of 1.5 ± 0.1 mg/L. At 4.7 ± 0.7 mg CIP/L, the performance of the AnMBR was reduced with lower COD removal and biogas production. In addition, VFA and SMP accumulation, biomass reduction, and an increase in pH were also observed. More Nitrogen containing compounds (N-compounds) and esters were found under CIP exposure, and p-cresol dominated the SMPs present when high CIP concentrations were added, with p-cresol concentrations as high as 49 µg/L. However, the overall performance of the AnMBR was still reasonable with an average of 78 ± 13% COD removal, and 50-76% of the CIP was removed when the CIP was fed at a concentration <1.5 mg/L. Biological degradation was the main mechanism for removing CIP, with a few intermediate compounds detected, but when CIP was added to the feed at 4.7 ± 0.7 mg/L, the removal of CIP decreased to < 20%. Activated carbon adsorption was found not to be very effective for the post-treatment of AnMBR effluents, and many fractions/compounds were shown not to be readily adsorbed; both the size fractions < 0.1 kDa, and about 134 kDa were difficult to remove. The identification of specific compounds in the effluent showed an excellent removal of N-compounds, phenolic compounds and CIP; in contrast, alkanes, alkenes, and esters were hard to remove.